The rin, nor and Cnr spontaneous mutations inhibit tomato fruit ripening in additive and epistatic manners. (May 2020) - Wang, Rufang; Lammers, Michiel; Tikunov, Yury; Bovy, Arnaud G.; Angenent, Gerco C.; de Maagd, Ruud A.
Highlights: The spontaneous, gain-of-function alleles rin and nor function additively in repressing tomato fruit ripening. The spontaneous Cnr mutant allele is epistatic to rin and nor mutations. The function of the genes and their spontaneous mutant alleles need to be evaluated separately, as the latter produced gain-of-function alleles. Abstract: Tomato fruit ripening is regulated by transcription factors (TFs), their downstream effector genes, and the ethylene biosynthesis and signalling pathway. Spontaneous non-ripening mutants ripening inhibitor ( rin ), non-ripening ( nor ) and Colorless non-ripening ( Cnr ) correspond with mutations in or near the TF-encoding genes MADS-RIN, NAC-NOR and SPL-CNR, respectively. Here, we produced heterozygous single and double mutants of rin, nor and Cnr and evaluated their functions and genetic interactions in the same genetic background. We showed how these mutations interact at the level of phenotype, individual effector gene expression, and sensory and quality aspects, in a dose-dependent manner. Rin and nor have broadly similar quantitative effects on all aspects, demonstrating their additivity in fruit ripening regulation. We also found that the Cnr allele is epistatic to rin and nor and that its pleiotropic effects on fruit size and volatile production, in contrast to the well-known dominant effect on ripening, are incompletely dominant, or recessive.